Metadata creation: Application for Thai Lanna historical and traditional archives - Techawut C. (2014)
This paper describes the process of metadata creation of the Thai Lanna historical and traditional archives (shortened to the Lanna Archives) by applying the Singapore Framework for Dublin Core Application Profiles. Its metadata model for scholarly works based on the Functional Requirements for Bibliographic Records (FRBR) is adapted to create a data model and metadata scheme for the Lanna Archives. The proposed metadata scheme provides the level of detail which describing digital Lanna Archives require and also supports information consistency and information sharing. © 2010 Springer-Verlag.